Manure properties, soil conditions and managerial factors regulate greenhouse vegetable yield with organic fertilizer application across China - Xiang, Yangzhou; Li, Yuan; Luo, Xuqiang; Liu, Ying; Yue, Xuejiao; Yao, Bin; Xue, Jianming; Zhang, Leiyi; Fan, Jing; Xu, Xiuyue; Li, Yonghua (Frontiers in Plant Science, 2022)
To better understand the responses of vegetable yields in a greenhouse system to organic fertilizer through a quantitative evaluation based on peer-reviewed journal articles and in consideration of environmental managerial factors. We conducted a meta-analysis of 453 paired observations from 68 peer-reviewed journal articles to assess the response of vegetable yields in greenhouse vegetable systems in China to organic fertilization. Compared with the control (no organic fertilizer), organic fertilization significantly increased the yields of vegetables by 44.11% on average. The response of vegetable yields to organic fertilizer tended to increase with the increasing experimental duration. Organic fertilizer application had the greatest potential for leafy vegetables (+76.44%), in loamy soils (+53.94%), at moderate organic fertilizer carbon input levels (+54.13%), and in soils with moderate initial soil total nitrogen levels (+50.89%). Aggregated boosted tree analysis indicated that organic fertilizer carbon inputs, vegetable type and experimental duration were the predominant factors that manipulated the response of vegetable yields to organic fertilizer application. The rational application of farmyard manure would be a promising strategy for increasing vegetable yields in greenhouse vegetable systems in China. Factoring in vegetable type, carbon and nitrogen inputs of organic fertilizer, and soil texture would benefit vegetable yields with the application of organic fertilizer.